Aladdin (Step into reading. Step 2 book, ,, 2019)
A retelling of the adventures of Aladdin, who, with the aid of a genie from a magic lamp, fights an evil sorcerer and wins the hand of a beautiful princess.

The librarian of Auschwitz (Thorndike Press large print mini-collections, ,, 2019)
Based on the experience of real-life Auschwitz prisoner Dita Kraus, this is the incredible story of a girl who risked her life to keep the magic of books alive during the Holocaust. Fourteen-year-old Dita is one of the many imprisoned by the Nazis at Auschwitz. Taken, along with her mother and father, from the Terezín ghetto in Prague, Dita is adjusting to the constant terror that is life in the camp. When Jewish leader Freddy Hirsch asks Dita to take charge of the eight precious volumes the prisoners have managed to sneak past the guards, she agrees. And so Dita becomes the librarian of Auschwitz.

Insignificant events in the life of a cactus (Life of a cactus, 1, 1, 2019)
"Aven Green loves to tell people that she lost her arms in an alligator wrestling match, or a wildfire in Tanzania, but the truth is she was born without them. And when her parents take a job running Stagecoach Pass, a rundown western theme park in Arizona, Aven moves with them across the country knowing that she'll have to answer the question over and over again. Her new life takes an unexpected turn when she bonds with Connor, a classmate who also feels isolated because of his own disability, and they discover a room at Stagecoach Pass that holds bigger secrets than Aven ever could have imagined. It's hard to solve a mystery, help a friend, and face your worst fears. But Aven's about to discover she can do it all . . . even without arms"--

I Survived the Bombing of Pearl Harbor, 1941 (I survived, 4, 1, 2017)
Visiting his favorite Hawaiian beach when Japanese forces suddenly attack Pearl Harbor, eleven-year-old Danny Crane struggles through the smoke, destruction, and chaos to make his way back home.

Mary Poppins (Mary Poppins series, 1, 1, 1997)
A blast of wind, a house-rattling bang, and Mary Poppins arrives at Number Seventeen Cherry Tree Lane. Quicker than she can close her umbrella, she takes charge of the Banks children--Jane, Michael, and the twins--and she changes their lives forever.
Mary Poppins , Mary Poppins comes back , Mary Poppins opens the door , Mary Poppins in the park.

I survived the shark attacks of 1916 (I survived (Graphic novels), 2, 1, 2017)
In July, 1916, Chet Roscow is fascinated by news accounts of the great white shark said to be attacking people along the New Jersey shore not far from his home, but when he goes swimming in Matawan Creek he discovers the truth of the stories.

Bridge to Terabithia (Recorded Books, Inc., HarperCollins Pub, Recorded Books, Playaway Digital Audio, HarperCollins, HarperTrophy, An imprint of HarperCollins Publishers, Harper Children's Audio, 1987)
The life of a ten-year-old boy in rural Virginia expands when he becomes friends with a newcomer who subsequently meets an untimely death trying to reach their hideaway, Terabithia, during a storm. This Newbery Medal-winning novel by bestselling author Katherine Paterson is a modern classic of friendship and loss.Jess Aarons has been practicing all summer so he can be the fastest runner in the fifth grade. And he almost is, until the new girl in school, Leslie Burke, outpaces him. The two become fast friends and spend most days in the woods behind Leslie's house, where they invent an enchanted land called Terabithia. One morning, Leslie goes to Terabithia without Jess and a tragedy occurs. It will take the love of his family and the strength that Leslie has given him for Jess to be able to deal with his grief.In addition to being a Newbery Medal winner, Bridge to Terabithia was also named an ALA Notable Children's Book and has become a touchstone of children's literature, as have many of Katherine Paterson's other novels, including The Great Gilly Hopkins and Jacob Have I Loved.Supports the Common Core State Standards
1. Jesse Oliver Aarons, Jr. --, 2. Leslie Burke --, 3. Fastest kid in the fifth grade --, 4. Rulers of Terabithia --, 5. Giant killers --, 6. Coming of Prince Terrien --, 7. Golden room --, 8. Easter --, 9. Evil spell --, 10. Perfect day --, 11. No! --, 12. Stranded --, 13. Building the bridge.

Goodnight Moon (Over the Moon, ,, 1975)
Goodnight to each of the objects in the great green room: goodnight chairs, goodnight comb, goodnight air.
Gift/Memorial Book : Amy Armitage, Gift/Memorial Book : Jeremy Kyle Stodgill, Gift/Memorial Book : Carol A. Cardenas

The hammer of thor (Magnus Chase and the gods of Asgard, 2, 1, 2016)
"Thor's hammer is missing again. The thunder god has a disturbing habit of misplacing his weapon-- the mightiest force in the Nine Worlds. This time the hammer isn't just lost, it has fallen into enemy hands. If Magnus Chase and his friends can't retrieve the hammer quickly, the mortal worlds will be defenseless against an onslaught of giants. Ragnarok will begin. The Nine Worlds will burn. Unfortunately, the only person who can broker a deal for the hammer's return is the gods' worst enemy, Loki-- and the price he wants is very high"-- Provided by publisher.

The tiger rising (Listening Library, Candlewick Press, Scholastic, 2009)
"In one morning, Rob Horton discovers a tiger in a cage and a girl who speaks her mind. It's then that he begins to understand that some things - like memories, and heartache, and tigers - can't be locked up forever" -- back cover.

The phantom tollbooth (Alfred A. Knopf, Epstein & Carroll; distributed by Random House, Midwest Tape, distr, Bullseye Books, RANDOM, Random House Children's Books, Random House/Listening Library, Scholastic, HarperCollins Publishers, Books on Tape, 2008)
One day Milo finds an enormous and mysterious package in his room. A phantom tollbooth, with a map to a weird world beyond! So Milo sets off on a fantastic voyage in which he meets: the not so wicked Witch, Faintly Macabre, Alec Bings who sees through things, and the watchdog, Tock, who ticks.
1: Milo , 2: Beyond expectations , 3: Welcome to Dictionopolis , 4: Confusion in the market place , 5: Short shrift , 6: Faintly Macabre's story , 7: Royal banquet , 8: Humbug volunteers , 9: It's all in how you look at things , 10: Colorful symphony , 11: Dischord and Dynne , 12: Silent Valley , 13: Unfortunate conclusions , 14: Dodechedron leads the way , 15: This way to infinity , 16: Very dirty bird , 17: Unwelcoming committee , 18: Castle in the air , 19: Return of rhyme and reason , 20: Good-bye and hello.

By the shores of Silver Lake (Little house (Laura Ingalls Wilder), 5, 1, 1953)
The adventures of Laura Ingalls and her family continue as they move from their little house on the banks of Plum Creek to the wilderness of the unsettled Dakota Territory. Ma and the girls follow Pa west by train where they make their home at a rough railroad camp and plan for their own homestead.
Unexpected Visitor , Grown Up , Riding in the Cars , End of the Rails , Railroad Camp , The Black Ponies , The West Begins , Silver Lake , Horse Thieves , The Wonderful Afternoon , Payday , Wings Over Silver Lake , Breaking Camp , The Surveyors' House , The Last Man Out , Winter Days , Wolves on Silver Lake , Pa Finds the Homestead , Christmas Eve , The Night Before Christmas , Merry Christmas , Happy Winter Days , On the Pilgrim Way , The Spring Rush , Pa's Bet , The Building Boom , Living in Town , Moving Day , The Shanty on the Claim , Where Violets Grow , Mosquitoes , Evening Shadows Fall.

The story of Ferdinand (Reading Beyond the Basal, ,, 1987)
Ferdinand the bull likes to sit quietly and smell the flowers, but one day he gets stung by a bee and his snorting and stomping convince everyone that he is the fiercest of bulls. Includes read-along disc in English or Spanish.

Are you there God? It's me, Margaret (Laurel-leaf books, ,, 1986)
Faced with the difficulties of growing up and choosing a religion, a twelve-year-old girl talks over her problems with her own private God.

Diary of an awesome friendly kid: rowley jefferson's journal (Diary of an awesome friendly kid, 1, 1, 2019)
"In his first journal, middle schooler Rowley Jefferson, Greg Heffley's sidekick, records his experiences and misguided decision to write a biography of Greg, who, in his own mind, is destined to become rich and famous."

These happy golden years: Little house series (Little house (Laura Ingalls Wilder), 8, 1, 1953)
"Laura's teaching position forces her to live away from home for the first time. Only one thing gets her through the lonely weeks - every weekend, Almanzo Wilder arrives at the school to take Laura home for a visit"--P. [4] of cover..

Broken Pride (Bravelands. Original series, 1, 1, 2018)
A lion cast out from his tribe. An elephant who can read the bones of the dead. A baboon rebelling against his destiny.Together, they must heed the call of the wild. For generations, the animals of the African plains have followed a single rule: only kill to survive. But when an unthinkable act of betrayal shatters the peace, the fragile balance between predators and prey will rest in the paws of three unlikely heroes.

Tales of a fourth grade nothing (Fudge books, 1, 1, 1986)
Peter finds his demanding two-year-old brother an ever increasing problem. Living with his little brother, Fudge, makes Peter feel like a fourth grade nothing. Fudge is never far from trouble. He's a two-year-old terror who gets away with everything-and Peter's had enough. When Fudge walks off with Dribble, Peter's pet turtle, it's the last straw.
Big winner , Me. and Mrs. Juicy-O , Family dog , My brother the bird , Birthday bash , Fang hits town , Flying train committee , TV star , Just another rainy day , Dribble!

M. C. Higgins, the great (Laurel-leaf books, ,, 1976)
As a slag heap, the result of strip mining, creeps closer to his house in the Ohio hills, fifteen-year-old M. C. is torn between trying to get his family away and fighting for the home they love.

On the Banks of Plum Creek (Little house (Laura Ingalls Wilder), 4, 1, 1965)
"Laura and her family find a new home in Walnut Grove, Minnesota, where the nearby creek and swimming hole lure Laura with dangerous, yet thrilling adventures. Too soon, their life is threatened when prairie fires and other strange events jeopardize their crops."
The door in the ground , The house in the ground , Rushes and flags , Deep water , Strange animal , Wreath of roses , Ox on the roof , Straw-stack , Grasshopper weather , Cattle in the hay , Runaway , The Christmas horses , A merry Christmas , Spring freshet , Footbridge , The wonderful house , Moving in , The old crab and the bloodsuckers , The fish-trap , School , Nellie Oleson , Town party , Country party , Going to church , The glittering cloud , Grasshopper eggs , Rain , The letter , The darkest hour is just before dawn , Going to town , Surprise , Grasshoppers walking , Wheels of fire , Marks on the slate , Keeping house , Prairie winter , The long blizzard , The day of games , The third day , The fourth day , Christmas Eve.